Activation of JAK2 kinase mediated by the interleukin 6 signal transducer gp130. - Narazaki, M (1994)
The interleukin 6 receptor-associated signal transducer, gp130, is shared by receptor complexes for leukemia inhibitory factor, oncostatin M, ciliary neurotrophic factor, and interleukin 11. We show here that JAK2 kinase is rapidly tyrosine phosphorylated in mouse embryonic stem cells whose pluripotentiality is maintained only by gp130-sharing cytokines after stimulation that is known to induce gp130 homodimerization. JAK1 is also tyrosine phosphorylated, but to a lesser extent, under the same conditions. Comparable results are obtained with hemopoietic lineage cells such as myeloid leukemic M1 cells and pro-B-cell line-derived transfectants expressing gp130, the former of which differentiate into macrophages after stimulation of gp130 and the latter of which initiate DNA synthesis. gp130-dimerizing stimulus upregulates kinase activity of JAK2 as revealed by immunocomplex kinase assay. Deletion or point mutation in the membrane-proximal cytoplasmic motifs in gp130 that are conserved in the hemopoietic cytokine receptor family results in the loss of tyrosine phosphorylation of JAK2, which coincides with the lack of signal transducing capability of gp130 mutants.